PENYELIDIKAN TINDAK PIDANA KORUPSI DI BIDANG PERTANAHAN DI KEJAKSAAN NEGERI DELI SERDANG - Khairur Rahman Nasution; Triono Eddy; Didik Miroharjo (Universitas Islam Negeri Sumatera Utara, 2023)
ABSTRACTThe increase in corruption crimes in the land sector has had a very bad impact because it is very detrimental to the state. Corruption can no longer be classified as an extraordinary crime. In addition to causing losses to the state, it also affects the life of the nation and state. Government policies in dealing with eradicating corruption include the Decree of the People's Correctional Assembly of the Republic of Indonesia Number XI/MPR/1998 concerning the Implementation of a State that is Clean and Free of Corruption, Collusion and Nepotism. However, in 1999 the government issued Law Number 28 of 1999 concerning State Administration Clean and Free from Corruption, Collusion and Nepotism and Law Number 31 of 1999 concerning Eradication of Corruption Crimes. Various ways by individuals and officials to commit acts of corruption include those carried out including in the Government Land section, namely the Honorarium budget fund for structuring and inventorying land assets and resolving land conflicts and monitoring government land issues. That is why the author here is interested in studying and conducting research with the title